PENGGUNAAN GEOGEBRA DALAM STATISTIKA DI ERA DIGITAL - Tika Dwi Nopriyanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The current technological development is very rapid. This is marked by the number of applications that appear to facilitate human activities, one of which is learning activities. Geogebra is one application or media used in learning mathematics, especially on the material, algebra, trigonometry, geometry, calculus and statistics. Learning and teaching activities (KBM) on statistical materials using Geogebra media make the KBM process more enjoyable especially in the material of pie chart, histogram, median, mode, mean, kuarti vaians, standard deviation and histogram. This is because the use of learning media KBM well will present a different learning susana and not boring.